Heart failure classification based on resting ejection fraction does not display a unique exercise response pattern. (1st April 2023) - Wernhart, Simon; Papathanasiou, Maria; Rassaf, Tienush; Luedike, Peter
Abstract: Background: Heart failure with preserved (HFpEF), mildly reduced (HFmrEF) and reduced (HFrEF) ejection fraction (EF) remains a controversial categorization. Whether these three categories reflect a distinct pattern of exercise limitation in cardiopulmonary exercise testing (CPET) needs to be investigated. We aimed to analyze whether CPET variables differ between all heart failure categories (HF). Methods: We analyzed CPET variables of stable HFpEF ( n = 123), HFmrEF ( n = 31), and HFrEF ( n = 153; 74 patients with and 79 patients without left ventricular assist device, LVAD) patients. The association between HF and peak oxygen consumption (VO2peak ) was used as a primary outcome, while the association between HF, oxygen uptake efficiency slope (OUES), and increase of O2 pulse (ΔO2 pulse) were analyzed as secondary outcomes. Results: VO2peak displayed a consistent decline across all HF categories (19.8 ml ± 6.2/kg/min vs. 17.5 ± 7.9 ml/kg/min vs. 13.7 ± 4.0 ml/kg/min, p < 0.001). OUES only showed differences between HFpEF and HFrEF (1.8 ± 0.6 vs. 1.4 ± 0.5, p < 0.001) as well as HFmrEF and HFrEF (1.9 ± 0.9 vs. 1.4 ± 0.5, p = 0.004). ΔO2 pulse differed between HFpEF and HFrEF (7.7 ± 3.5 ml/beat/kg*100 vs. 5.5 ± 3.0 ml/beat/kg*100, p < 0.001) as well as HFpEF and HFmrEF (7.7 ± 3.5 ml/beat/kg*100 vs. 6.3 ± 4.1 ml/beat/kg*100, p = 0.049). Outcome variables did not differ between HFrEF with and without LVAD support (VO2peak : p = 0.364, OUES: p = 0.129, ΔO2 pulse: p = 0.564). Conclusions: HF did not display a distinct CPET profile. Thus, EF-based categorization does not entirely reflect exercise limitations. CPET variables could contribute to better characterize HF phenotypes. Graphical abstract: Differential response of variables of cardiopulmonary exercise testing across ejection fraction in heart failure. HFpEF: Heart failure with preserved ejection fraction. HFmrEF: Heart failure with mildly reduced ejection fraction. HFrEF+/-LVAD: Heart failure with reduced ejection fraction with/without left ventricular assist device. VO2peak : Peak oxygen consumption. OUES: Oxygen uptake efficiency slope. ΔO2 pulse: Difference between resting and peak O2 pulse. Unlabelled Image Highlights: VO2peak declines with HF category. ΔO2 pulse and OUES show a differential response in HF categories. Variables of cardiopulmonary exercise testing should be used to delineate exercise limitations of heart failure phenotypes.